Taxonomic notes on the group of Mischocyttarus heliconius Richards 1941, with description of four new species (Hymenoptera: Vespidae, Polistinae) - Pinheiro, Mileudiane O.; Silveira, Orlando T. (Zootaxa, 2023)
Mischocyttarus heliconius was described by Richards (1941), being initially assigned to subgenus Kappa, and later to Clypeopolybia. That author subsequently described other similar species, and Silveira (2008) conceived the group as also including M. iperuae Richards, M. sericeus Richards, M. chanchamayoensis Richards, and M. piger Richards. However, the latter species is not a member of this group, which otherwise can be easily recognized by morphological characters. Three of these species were retrieved as forming a monophyletic group by Silveira (2008), but relations with other groups in Mischocyttarus are uncertain. Types and new material of the M. heliconius group are here revised, with addition of four new species (M. gorotire sp. nov., M. ipixuna sp. nov., M. luciliae sp. nov., M. ticuna sp. nov.), and a new identification key is presented. Mischocyttarus piger Richards is reassigned to the group of M. iheringi Zikán in the subgenus Haplometrobius Richards.